1921
DOI: 10.5962/bhl.title.24203
|View full text |Cite
|
Sign up to set email alerts
|

Civic science in the home

Abstract: To the many science teachers who have been active in developing general science from its early beginnings to its present state, the authors make full acknowledgment for much help and inspiration. Acknowledgment for illustrative material is made in the text. The drawings were nearly all made by Mr. F. M. Wheat, of the George Washington High School, New York. The following teachers have carefully read the entire proof and made many valuable suggestions :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1933
1933
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The optimum conditions for the quantitative use of the Pauli reaction were clearly demonstrated by KOESSLER and HANKE in 1919 (6), and its application to the estimation of carnosine in muscle was effected almost simultaneously by CLIFFORD (7) and by HUNTER (8), of whom the latter explored carefully the very difficult question of the specificity of the test as a measure of carnosine (9). He concluded that of a number of possible interfering substances which he examined, none were likely to be serious sources of error save, in certain circumstances, histidine.…”
mentioning
confidence: 99%
“…The optimum conditions for the quantitative use of the Pauli reaction were clearly demonstrated by KOESSLER and HANKE in 1919 (6), and its application to the estimation of carnosine in muscle was effected almost simultaneously by CLIFFORD (7) and by HUNTER (8), of whom the latter explored carefully the very difficult question of the specificity of the test as a measure of carnosine (9). He concluded that of a number of possible interfering substances which he examined, none were likely to be serious sources of error save, in certain circumstances, histidine.…”
mentioning
confidence: 99%
“…22, the absence of the nucleolar organizing region on the ring chromosome no. 22 was reported by Hunter et al (1977), Funderburk et al (1979), and Fowler et al (1980. But in the present case, the presence of the nucleolar organizing region on the ring chromosome no.…”
Section: Remarks and Conclusionmentioning
confidence: 60%
“…22 has been reported on at least 29 patients (Brookfield and Walker 1976;Rethore et al 1976;Hunter et al 1977;Howard-Peebles 1977;Palmer et al 1977;Funderburk et al 1979;Fryns and Berghe 1979;Fowler et al 1980). Several patients manifested a distinctive features consisting of the mental retardation with verbal delay, epicanthal folds, full eyebrows, large ears, arched palate and/or high palate, large nose, low nasal bridge, thick is, hypoplastic mandible, skeletal anomalies, syndactyly, ataxic gait and seizure (Table I).…”
Section: Remarks and Conclusionmentioning
confidence: 99%
“…[168] to [170] which allow the necessary amount of information to be gained from the minimum number of experiments. When experiments are conducted in a sequential manner, discrimination between rival kinetic models is possible [171]- [173]. In the sequential method, discrimination amongst rival models is obtained by repeated estimation of the parameters for each model, after which some are eliminated by the application of chosen criteria.…”
Section: H Automated Reactorsmentioning
confidence: 99%